Dream themes and rejection sensitivity of individuals with and without borderline personality disorder: a comparative study - Faraji, Haydeh (The European Research Journal, 2024)
Objectives: This study aims to determine how the dream themes of borderline personality disorder patients differ from those of without borderline personality disorder diagnosis and the mediating role of rejection sensitivity in this differentiation process. Methods: The convenience sampling method was used in the study, and the participants were 79 female borderline patients diagnosed with semi-structured interviews with criteria of DSM-5 and 79 female individuals who had not received a psychological diagnosis before and at the study interviews. Sociodemographic Information Form, Dream Themes Scale, Borderline Personality Questionnaire, and Rejection Sensitivity Scale were used in the study. Linear Regression Analysis, Hierarchical Regression Analysis, and Independent Groups T-Test were used during the investigations. Results: Borderline personality disorder patients scored higher in all sub-dimensions of the dream themes scale and rejection sensitivity scale than the control group. Borderline personality traits predicted rejection sensitivity. Borderline personality traits and rejection sensitivity together predicted dream themes. Borderline personality predicts anxiety dreams, fear dreams, and experience dreams, and rejection sensitivity mediates these predictive relationships. Conclusions: The dreams of borderline personality disorder patients have negative content covered by the impact of experiences sub-dimension on dream themes, as they contain reflections of negative content in beliefs, thoughts and emotions related to their daily lives. Rejection sensitivity plays a mediator role in borderline patient’s dreams. The study results show that it would be beneficial not to ignore the content of dreams in patients with borderline personality disorder, considering the relationship of negative dreams with daily functioning, dissociative symptoms, self-harming behaviors, and suicide attempts. Results also indicate that it might be beneficial to target rejection sensitivity to reduce aggravating dream contents.